Dialysate color and its role in presumptive diagnosis of dimorphic fungi in peritoneal dialysis associated fungal peritonitis - Narain, Upma; Gupta, Arvind (International Journal of Advances in Medicine, 2017)
Background: Fungal peritonitis is a rare but serious complication of peritoneal dialysis (PD). Dimorphic fungi are described in peritonitis at a much lower percentage than yeasts are, but their involvement in it is growing. Methods: The study was based on the analysis of available data over a period of 16 years. The sample size was of 421 ESRD patients on CAPD. We retrospectively identified 72 cases of fungal peritonitis. In the present study we assessed the frequency of dimorphic fungi as a single pathogen, its association with the dialysate colour along with the predictors and its impact on the outcome of the patients. Results: In between January 2000 and October 2016, in present retrospective study, we identified 72 episodes of peritoneal dialysis associated with fungal peritonitis. Among the 72 fungal episodes, 83.3% were Candida species, 1.5% were yeast and the remaining 15.2% were dimorphic fungi. The macrolevel observations of dialysate showed greyish, blackish, greenish, pinkish, cloudy, bluish green and cloudy colours that developed due to the pigmentation of fungi and fungal spores. The Aspergillus species predominates amongst the dimorphic fungi. Outcome analysis revealed that the loss of life (14.7%) was more frequent in diabetics while the reinsertion of catheter failed in cases of glomerulonephritis. It was also noticed that de novo infections were more frequent among the diabetics and that the previous bacterial peritonitis episode was the strongest predictor amongst them all. Conclusions: The premise of the current study illustrates the fact that the dialysate colour can be put to use as an early warning system and by combining the macroscopic observations of the dialysate with the results of microscopy and culture, the diagnosis of Fungal peritonitis due to dimorphic fungi will not be missed. Also worth noting is the point that an early assessment of predictors alongside that of an antifungal coverage can lead to a reduction in the rates of morbidity which in turn will shorten the stay in hospital. This will prevent any further nosocomial infection, antifungal resistance and chances of treatment failure.